Conservation Strategies on the Abandoned Towns in the Former Tin Mining Towns in Lembah Kinta, Perak - Shariff, Mohd Rifzal Mohd; Endut, Esmawee; Alias, Ahmad Faisal; Jaafar, NorHaslina (MAJ - Malaysia Architectural Journal, 2022)
This paper focuses on how the conservation of abandoned towns in the former tin mining town in Malaysia which could contribute to safekeeping Malaysian cultural heritage entity in order to regenerate cultural heritage entity. Pekan Papan, Perak has been chosen as a case study due to its distinctive characteristics as an early tin mining towns and its historical significance of Malaysia’s economy activities and its attribution to mix culture heritage. The qualitative method based on Case study research will explore, identify and evaluate the tangible elements in the selective former tin mining old towns as a cultural heritage resource by reviewing the definitions and concept of physical characters and cultural value in attributes to the identity of a place. The recognition of people towards the presence of distinctive elements, from the understanding of the built forms and its activities will enhance the unique characteristic which could be identifiable, recognized and remembered by people an as essence of heritage, worth to conserve and to regenerate the cultural heritage value.